FDI inflow, current account balance, inflation and interest rate: How do they impact the Malaysian economy? - Kandiah, Siva Kumar (Universiti Utara Malaysia, 2009)
This article seeks to find which of the macroeconomic variables among FDI inflow,current account balance, inflation and interest rate play a significant role in economic growth in Malaysia using the SPSS Regression method for a time period of 14 years from 1995 to 2008 (Oct). The results of the research indicated that FDI and inflation are not significantly related to economic growth in Malaysia during the period of study. However, CA balance and BLR are significant determinants of economic growth of Malaysia during the period of study. Inflation was noted to have a negative relationship while FDI, CA Balance and BLR were all positively related to economic growth in Malaysia.